#TITLE_ALTERNATIVE# - ROSALINA SIANTURI (NIM 15106042); Pembimbing: Dr. Ir. Dwi Wisayantono, MT, dan Intan Hayati, DORMATUA
Indonesia is the archipelagic state that consist of + 17,508 islands as well as the coastal territory and sea reached 63% of the Indonesian territory on the whole. In relation to the phenomenon of the dynamics of the coast like the abrasion and the sedimentation, the coastal territory was the affected territory direct the impact of the dynamics of this coast. With the existence of the phenomenon of the dynamics of this coast then will affect the area of the coastal territory. The ratio of the land was formed from the territory component and the inhabitants. The area of the territory that tended to continue to even decrease and the number of inhabitants that increased influenced big the ratio of the land and had an impact on the pattern of the life of the community. The dynamics size of the coast was reduced from the image the Indramayu satellite of the territory of the Regency coast in 1994 and 2007. Relations between the dynamics of the coast and the social aspect of the Indramayu coastal community could be seen from the value and the association of the correlation geografikal whereas for the aspect of economics was seen from the value of regression and location quotient. These values were made the reference in analysing the condition for economics and social resulting from the abrasion.